2(4x+1)-4(5-x)-5=2(10-x)

Simple and best practice solution for 2(4x+1)-4(5-x)-5=2(10-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4x+1)-4(5-x)-5=2(10-x) equation:



2(4x+1)-4(5-x)-5=2(10-x)
We move all terms to the left:
2(4x+1)-4(5-x)-5-(2(10-x))=0
We add all the numbers together, and all the variables
2(4x+1)-4(-1x+5)-(2(-1x+10))-5=0
We multiply parentheses
8x+4x-(2(-1x+10))+2-20-5=0
We calculate terms in parentheses: -(2(-1x+10)), so:
2(-1x+10)
We multiply parentheses
-2x+20
Back to the equation:
-(-2x+20)
We add all the numbers together, and all the variables
12x-(-2x+20)-23=0
We get rid of parentheses
12x+2x-20-23=0
We add all the numbers together, and all the variables
14x-43=0
We move all terms containing x to the left, all other terms to the right
14x=43
x=43/14
x=3+1/14

See similar equations:

| 5(x+3)+10=2(x+6) | | 6x+8x+2x=10+10+10 | | r-183=17 | | (2/(3u))+(7/(5u))=1 | | 10/15+3y=5y-2/15 | | -6-7=6x+89 | | 4+3x-7=3x+2-x | | 6n-10=2n+4 | | 6y-3=14 | | -6(2k-3)=-7k | | 2(x+3)=-8x+6 | | v/12-19=-27 | | p+23=2p | | 32÷c=2 | | 7x-46=22 | | 2x+7.5+63.9=180 | | 8r-6r=2+4r | | -9x-18=-63 | | p=2(p-12) | | 34÷n=14 | | 16+7n=3n-8 | | c-3/c=9/10 | | 2x-3(x-1)=-12 | | 14x+4=18. | | 8+6a=8a-8 | | -4b+10=-66 | | j=0 | | 7w+24=3 | | y+38=2(10y) | | 3=w/8*6 | | y+38=2y | | X²-11x-12=0 |

Equations solver categories